Developing a Campus Blended Learning Framework to Improve Adoption in Higher Educational Institutions in Southwestern Uganda - Kabarungi, Moreen; Ntwari Richard; Annabella Habinka Ejiri; Kawuma Simon (AI Society & STMIK Indonesia, 2025)
Despite the potential benefits of blended learning in higher education, adoption rates in Ugandan universities remain critically low at 29.1%, with significant barriers including inadequate infrastructure, limited institutional support, and mental health challenges affecting both educators and students. This study aimed to develop a Campus Blended Learning Framework (CBLF) to improve blended learning adoption in higher educational institutions in southwestern Uganda. A Design Science Research methodology was employed, incorporating both quantitative and qualitative approaches. Data were collected from three universities: Mbarara University of Science and Technology (MUST), Bishop Stuart University (BSU), and Kabale University (KAB). A total of 1,495 participants (1,051 students and 444 staff members) were surveyed using structured questionnaires based on the Complex Adaptive Blended Learning Framework (CABLF). Ten experts participated in qualitative interviews to evaluate the framework's usability and acceptability. The study identified six critical components for effective blended learning adoption: pedagogy, infrastructure, content, assessment, support, and mental health. Mental health emerged as a significant factor influencing all other components. The proposed CBLF integrates these elements while addressing the unique contextual challenges of developing countries. The Campus Blended Learning Framework provides a comprehensive approach to addressing low adoption rates of blended learning in southwestern Uganda's higher educational institutions. The framework's emphasis on mental health support and contextual adaptation makes it particularly suitable for developing country contexts.